Web-based business reporting: the influences drivers - Turmin, Siti Zaidah; Abdul Hamid, Fatima; Mohamad Ghazali, Nazli Anum (WorldConferences.net, 2014)
Web-based reporting is the reporting of financial and non-financial information provided by companies through the medium of corporate websites. Web-based reporting includes information of either a financial or non-financial nature that is not normally incorporated in the printed form of companies’ annual reports. Web-based reporting is vital for the corporate sector in presenting and disseminating business information to the stakeholders. Among the advantages of Web-based reporting compared to traditional paper-based reporting are innovative presentation of information, dynamic multimedia formats, wider and easier access to information for larger groups of users without selection, creating interest to potential investors and boosting corporate image, providing timeliness and interactive information with unlimited space as well as the faster and lower cost of information dissemination. Previously, the practice of Internet reporting in Malaysia was voluntary in nature, thus, leads to a lack of uniformity among companies in Malaysia in terms of the information disclosed and the way the information is presented. The inconsistencies of Web-based reporting practice among companies further raised problems of companies’ uncertainty concerning what information is to be displayed, difficulties to users in locating and finding information on corporate websites and difficulties to the regulators in tracking, monitoring, comparing and assessing Internet reporting practise of the companies. On 3rd of August 2009, Bursa Malaysia introduced a new listing rule under Bursa Malaysia Listing Requirement, Chapter 9, Paragraph 9.21 that requires the Malaysian public listed companies to have their own corporate websites. However, the new regulation can be said to be general, as the regulation does not mention the specific attributes of Web-based reporting that need to be presented on the corporate websites of the companies. Consequently, uniformity of Web-based reporting practice in Malaysia is still difficult to achieve. Thus, problems faced by companies, users and regulators may continue to arise. The inconsistency of Web-based reporting practice by Malaysian companies is expected to be caused by certain factors that influence the level of Web-based reporting practiced. This study intends to look into the specific company characteristics that influence the extent of Web-based reporting practice. The company characteristics examined are size of company, liquidity, profitability, leverage, activity sector and audit type. Data collection for the extent of Web-based reporting took place between 9th December 2008 and 18th February 2009, whereas data for the company characteristics were based on the year of 2008. Data were analysed using multiple regression. The results show that firm size and profitability were positively statistically significant at p<0.05. This revealed that an increase in company size and profitability will contribute to an increase in the extent of Web-based reporting. Furthermore, the industrial products sector was statistically significant at p<0.05, but negatively so. Therefore, the result shows that companies from the sector of industrial products have a low level of Web-based reporting practice. In fact, the extent of Web-based reporting practice is much lower as compared to other sectors. Other factors were found to be not statistically significant. This means that the extent of Web-based reporting is not influenced by these factors.